The Influence of Service Quality on Satisfaction Meulaboh Branch Employment BPJS Participants During Pandemic - Lusiana Sari, Vika (Ridwan Institute, 2021)
Consumer satisfaction is the most important thing to be considered by business people or businesses in order to maintain a sense of trust and consumer comfort. The government issued various policies, such as social distancing, work from home, and inviting people to stay at home. Restrictions on activities carried out by BPJS Employment at the Meulaboh branch by using online services in the form of LAPAK ASIK (service without physical contact) in order to reduce the spread of covid-19 to participants. Participant satisfaction can be considered with the quality of service provided, the quality of service that meets the expectations of participants is important. This study aims to determine the effect of service quality on the satisfaction of BPJS employment participants at the Meulaboh Branch. Service quality variables consist of Tangible, Empathy, Reliability, Responsiveness, and Assurance indicators. The type of research used is descriptive quantitative research and the sample used is 20 respondents. Data collection techniques using a questionnaire using google from. Data analysis used multiple linear regression. The results showed that the service quality variable had an effect on the satisfaction of participants of BPJS Employment at the Meulaboh Branch simultaneously. The independent variable is able to explain the relationship and its influence on the dependent variable as much as 87.7%. There is a partially significant effect on the service quality variable on customer satisfaction with a significance result of t(0.000) < 0.005.